A Study of Faculty Retention Factors in Educational Institutes in Context With ABET - Khan, Fazal Qudus; Buhari, Seyed M.; Tsaramirsis, Georgios; Rasheed, Saim (Frontiers in Education, 2021)
A typical higher education institute classically has all the five major constituents, i.e. current students, alumni, faculty members, employers and industrial advisory board. Expectations of the rest of the constituents are fully dependent on the faculty members, as they play a pivotal and backbone role in building up an educational institute, to a high repute. Faculty members provide the knowledge and skills necessary to students, to address market needs. Letting go of skilled, professional and enthusiastic faculty members can have a huge impact on any higher education institution’s reputation and in fulfilling the market needs. In this research, we explore the different influencing factors and criteria for retaining teaching staff at schools and higher education institutes. These criteria are then evaluated against Accreditation Board of Engineering and Technology (ABET) accredited institutes criteria data of “faculty” and “Institutional support”, to see the impact. Study shows that only very few faculty members leave the institution because of higher student-to-faculty ratio or denial of tenure. Also, most of institutions concentrate on providing reduced number of lecture hours per week to keep their faculty members happy and perform research at the institution. Out of 737 faculty members of 27 institutes included in this study, only 0.54% faculty members left ABET accredited institutions.